COMORBIDITIES IN PATIENTS WITH ISCHEMIC HEART DISEASE: GENDER DIFFERENCES - A. N. Sumin; E. V. Korok; A. V. Shcheglova; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Background. The problem of comorbidity in ischemic heart disease (IHD) has always been given increased attention, due to the high social significance of cardiovascular diseases. However, often the problem solution involved studying cardiac pathology along with concomitant diseases, such as diabetes mellitus, pulmonary or kidneys pathology, etc., but not a comprehensive approach, which takes into account all available comorbidities. An important issue that should be considered in the shift to the personalized medicine is the presence of gender differences, which varies greatly and depends on different correlations with specific comorbidities.Aim. To study gender differences in comorbidities in patients with IHD.Material and methods. 742 patients with IHD examined in the Research Institute for Complex Issues of Cardiovascular Diseases in 2011 before elective coronary by-pass surgery were included into the study. All the patients were divided into 2 groups depending on the gender: Group 1 – 147 females, Group 2 – 595 males.Results. The obtained results reported that women were commonly older than men and more often had excess body weight (p<0.001). The majority of current smokers were males (p<0.001). During preoperative preparation, the development of myocardial infarction (MI) was observed in 12.9% of women and 7.4% of men (p=0.031), while the history of MI was more often found in male patients (p=0.004). The evaluation of the severity of angina pectoris and chronic heart failure (CHF) revealed that in men the I and II functional classes (FC) of angina (p=0.057 and p=0.007, respectively) and stage I CHF (p<0.001) were prevailed, whereas women had angina FC 3-4 (p=0.005 and p=0.050, respectively) and stage IIa CHF (p<0.001). Women more often than men suffered from hypertension (p=0.01) and atrial fibrillation (p=0.024), while peripheral artery disease prevailed among men (p=0.022). The analysis of comorbidities showed that disorders of carbohydrate metabolism, thyroid disease, bronchial asthma and varicose disease were more common in female patients (p<0.05), whereas chronic hepatitis (p=0.079) and urolithiasis – in males (p=0.028). The comorbidity score did not differ significantly between the study groups  (p>0.05), wherein the average level of comorbidity score prevailed among men (70.4%) and women (66%).Conclusion. Detection of comorbidities in IHD patients based  on gender differences is advisable to improve both  the  immediate results of surgical management and further preventive measures.